2012
DOI: 10.1149/2.jes113585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Pickling Pretreatment on the Properties of Cerium Conversion Coating on AZ31 Magnesium Alloy

Abstract: The rare earth metal conversion coating process is recognized for its simple electrolyte composition, which is generally considered to be environmentally friendly. In this study, cerium conversion coatings were made in a cerium nitrate/hydrogen peroxide solution on AZ31 magnesium alloys after 20 s of pickling in hydrochloric acid (HCl) or hydrofluoric acid (HF) solutions. Results show that acid pickling in HF or HCl enhanced the adhesion and corrosion resistance of the cerium conversion coating. This enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…3f shows the selected area electron diffraction (SAED) pattern of the compact layer, which consisted of diffraction rings resulting from Ce (IV) oxide (CeO 2 ). 19,41 The thickness of the Ce oxide on the Ce-coated 0.5 wt% HF-and 11 wt% HF-pretreated AZ91D was around 160 nm and 40 nm, respectively. Moreover, craters were occasionally observed on the Ce-coated 0.5 wt% HF-pretreated coupon, as marked by the arrow in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3f shows the selected area electron diffraction (SAED) pattern of the compact layer, which consisted of diffraction rings resulting from Ce (IV) oxide (CeO 2 ). 19,41 The thickness of the Ce oxide on the Ce-coated 0.5 wt% HF-and 11 wt% HF-pretreated AZ91D was around 160 nm and 40 nm, respectively. Moreover, craters were occasionally observed on the Ce-coated 0.5 wt% HF-pretreated coupon, as marked by the arrow in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 Su et al demonstrated that comparing to the HCl pretreatment, the pretreatment in HF solution remarkably reduced the amounts of blisters and effectively enhanced the adhesion and corrosion resistance of the Ce conversion coating on the AZ31. 41 However, HF is one of the dangerous acids and potentially causes severe burns and systemic toxicity. 42 As a consequence, efforts were made in this study looking for a substitute for HF solution.…”
mentioning
confidence: 99%
“…Blisters are common defects on cerium conversion coatings. [14][15][16][17][18] Further immersion resulted in an increase in the amount and size of the blisters. Such blisters can lead to local detachment of the coating.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…The two-layer coating was composed of an inner porous layer with Mg/Al oxide and hydroxide and an outer compact layer of cerium oxide (CeO 2 ). [14][15][16]18 Blisters are related to the breakdown of the CeO 2 layer due to hydrogen evolution. In this study, the cerium conversion coatings were conducted on AZ91 magnesium plates in cerium nitrate aqueous solution with H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] It is well known that pure CeO 2 is pale yellow probably due to Ce(IV) -O(-II) charge transfer. 13 Whereas, CeO 2 color is sensitive that depends on the oxygen deficiency.…”
mentioning
confidence: 99%